STUDI KORELASI ANTARA BINUSMAYA DENGAN KEPUASAN MAHASISWA UNIVERSITAS BINA NUSANTARA: STUDI KASUS PROGRAM STUDI KOMPUTERISASI AKUNTANSI - Sukawati, Anak Agung Nyoman; Tania, Wandari; Putri, Tina Carolina Antoro; Chandra, Billy (CommIT (Communication and Information Technology) Journal, 2007)
The article purpose was to know the relation between BinusMaya with student satisfaction of Bina NusantaraUniversity. The used research method was survey method, corelational technique with collecting data using questioner.The research result was there is correlation coefficient + (0,4336) which mean there is positive relation and includingmedium category between BinusMaya with student satisfaction. Determination coefficient was 0,188 which means 18,8% of student satisfaction variation can be explain by BinusMaya variable. The conclusion was there is positive correlationbetween BinusMaya with the student satisfaction, which means the more effective of BinusMaya so the student satisfactionis getting higher.Keywords: BinusMaya, student satisfaction, computerize accounting